2007
DOI: 10.1038/sj.mp.4002079
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of mutant human DISC1 in mice is associated with brain and behavioral abnormalities reminiscent of schizophrenia

Abstract: A strong candidate gene for schizophrenia and major mental disorders, disrupted-inschizophrenia 1 (DISC1) was first described in a large Scottish family in which a balanced chromosomal translocation segregates with schizophrenia and other psychiatric illnesses. The translocation mutation may result in loss of DISC1 function via haploinsufficiency or dominant-negative effects of a predicted mutant DISC1 truncated protein product. DISC1 has been implicated in neurodevelopment, including maturation of the cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
336
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(356 citation statements)
references
References 65 publications
20
336
0
Order By: Relevance
“…It may be necessary to explore the utility of temporal or spatial genetic knockdowns to gain information about the importance of a number of genes in schizophrenia. Recent work with DISC1 confirms the value of this approach (Hikida et al, 2007;Pletnikov et al, 2007).…”
Section: Animal Preparations and Their Use In Schizophrenia Drug Discmentioning
confidence: 71%
“…It may be necessary to explore the utility of temporal or spatial genetic knockdowns to gain information about the importance of a number of genes in schizophrenia. Recent work with DISC1 confirms the value of this approach (Hikida et al, 2007;Pletnikov et al, 2007).…”
Section: Animal Preparations and Their Use In Schizophrenia Drug Discmentioning
confidence: 71%
“…Although both groups identified increased lateral ventricle size in the absence of any change in total brain volume, Hikida et al 52 detected this abnormality only at 6 weeks of age and demonstrated, rather surprisingly, that by 3 months (when the transgene is no longer expressed) there is no detectable difference in lateral ventricle size between wildtype and transgenic animals. Pletnikov et al, 53 however, detected the increased lateral ventricle size in adult mice. Hikida et al 52 also found evidence for loss or reversal of normal brain asymmetry in animals expressing the transgene.…”
Section: The Phenotype Of Mouse Disc1 Variantsmentioning
confidence: 95%
“…Within this developmental window, transgene expression is similar to that of endogenous Disc1 in the forebrain, although endogenous Disc1 is also present at other locations throughout the brain and throughout development into adulthood (see subsequent sections). Ross and co-workers (Pletnikov et al 53 ) used essentially the same approach, but with an inducible expression system directed by the CaMKII promoter, and were able to detect expression from as early as embryonic day 15, suggesting that the CaMKII promoter may not be faithfully regulated.…”
Section: The Phenotype Of Mouse Disc1 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Disc1/Ndel1 interaction also competitively inhibits Ndel1 oligopeptidase activity (Hayashi et al, 2010). Finally, the balanced translocation disrupting the DISC1 gene described by Millar et al (2000) generates a truncated form of Disc1 protein reported to be unable to bind to Ndel1 Kamiya et al, 2005;Pletnikov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%